ANALISIS SISTEM MANAJEMEN PERSEDIAAN DENGAN MENGGUNAKAN SISTEM MICROSOFT BUSINESS SOLUTIONS NAVISION DAN TEKNOLOGI INFORMASI - Hendi Sama (Universitas Putera Batam, 2015)
The long term goal of this research is benefiting company in Kepulauan Riau Province regarding application of Microsoft Business Solution and information technology in doing their job. This research attempts to examine how these independent variabels affect inventory management system. This research uses 2 independent variables and 1 dependent variable. The impact of independent variable was analyzed by regression model. Results show that there are significant interrelated dependence relationships among variables.